O encontro entre Arte, Ciência, Técnica e Tecnologia: das inovações na pintura renascentista às produções imersivas contemporâneas - Oliveira, Mariana Vieira de (2024)
The Renaissance period was the great engine for science to navigate ever closer to modernity. It is a moment in European culture responsible for a more detailed perspective on nature studies and the application of new scientific methods that value worldly experience and man's answers to questions present in philosophy and science. However, “perspective” is no longer a term exclusive to the mathematical and geometric questions of the time and becomes part of a list of important artistic techniques during the Renaissance. During this period, unity is created, and then rupture comes. And it is in this unity that art and science are juxtaposed, to work together. It is through this joint work that many “revolutions” can be discovered in the world of art, from photography and cinema, to artistic production that promotes greater emancipation of the spectator from the passive observing role, in favor of creating spaces capable of manipulating sensations and feelings in “real time” and which will possibly never be repeated. This dissertation aims to observe the interactions between science and art in different periods, going through their shared production techniques, in which science lends means of production to the arts and vice versa, landing on the construction of art through science, in which the limit between the two is tenuous and dependent